Spin glass behavior in frustrated quantum spin system CuAl2O4 with a possible orbital liquid state. (15th February 2017) - Nirmala, R; Jang, Kwang-Hyun; Sim, Hasung; Cho, Hwanbeom; Lee, Junghwan; Yang, Nam-Geun; Lee, Seongsu; Ibberson, R M; Kakurai, K; Matsuda, M; Cheong, S-W; Gapontsev, V V; et al.
Abstract: CuAl2 O4 is a normal spinel oxide having quantum spin, S = 1/2 for Cu 2+ . It is a rather unique feature that the Cu 2+ ions of CuAl2 O4 sit at a tetrahedral position, not like the usual octahedral position for many oxides. At low temperatures, it exhibits all the thermodynamic evidence of a quantum spin glass. For example, the polycrystalline CuAl2 O4 shows a cusp centered at 2 K in the low-field dc magnetization data and a clear frequency dependence in the ac magnetic susceptibility while it displays logarithmic relaxation behavior in a time dependence of the magnetization. At the same time, there is a peak at 2.3 K in the heat capacity, which shifts towards a higher temperature with magnetic fields. On the other hand, there is no evidence of new superlattice peaks in the high-resolution neutron powder diffraction data when cooled from 40 to 0.4 K. This implies that there is no long-ranged magnetic order down to 0.4 K, thus confirming a spin glass-like ground state for CuAl2 O4 . Interestingly, there is no sign of structural distortion either although Cu 2+ is a Jahn–Teller active ion. Thus, we claim that an orbital liquid state is the most likely ground state in CuAl2 O4 . Of further interest, it also exhibits a large frustration parameter, f = | θ CW / T m | 67, one of the largest values reported for spinel oxides. Our observations suggest that CuAl2 O4 should be a rare example of a frustrated quantum spin glass with a good candidate for an orbital liquid state.